Autoimmune Interventions: Between (Bio)deconstruction and (Bio)politics - Hickman, Amy Katherine (Curtin University, 2023)
This thesis puts forward a reinterpretation of the political significance of Jacques Derrida’s concept of autoimmunity. Finding that the generalisation of autoimmunity cannot guarantee a normative politics, the thesis investigates that logic’s effects in the biopolitical thought of Judith Butler, Roberto Esposito, and Hannah Arendt. I argue that autoimmunity shows us that nothing is immune from politicisation, and instead multiplies the possibilities for what political thought and action could be and where they might appear.